Premature Hoisting Wire Rope Failure in Marine Deck Cranes: Investigating Diameter Mismatch, Two-Layer Spooling, and Sustainable Maintenance Strategies - Michael Rumopa (Journal of Marketing Management and Innovative Business Review, 2026)
Hoisting wire ropes are critical components of marine deck crane systems, directly affecting operational safety, lifting efficiency, and equipment reliability. This study investigates the causes of premature hoisting wire rope failure on the deck crane of MV Roslyn and proposes maintenance strategies to extend its service life. A qualitative case study approach was conducted based on field observations from July 2025 to February 2026. Data were obtained through direct observations, inspections of wire ropes, drums, and sheaves, maintenance records, lifting plans, and technical documentation. The results indicate that the hoisting wire rope operated for only 200–300 hours, substantially below the expected service life of 1,300–1,500 hours. The main contributing factors were incompatibility between the wire rope diameter and the drum and sheave groove dimensions, the use of a two-layer spooling system, and inadequate lubrication practices. These conditions increased contact stress, friction, fatigue, deformation, and structural deterioration of the wire rope. To address these issues, corrective measures were implemented, including improving lubrication practices and recommending dimensional adjustments to the drum and sheave grooves, as well as adopting a single-layer spooling configuration. Enhanced lubrication alone increased wire rope service life to approximately 600–700 operating hours. Furthermore, predictive maintenance based on operating hours was found to support timely replacement planning while maintaining vessel operational efficiency.